HPV-based strategy in follow-up of patients treated for high-grade cervical intra-epithelial neoplasia: 5-year results in a public health surveillance setting. (March 2017) - Garutti, P.; Borghi, C.; Bedoni, C.; Bonaccorsi, G.; Greco, P.; Tognon, M.; Martini, F.
Abstract: Objective: Human papillomavirus (HPV) DNA testing is used increasingly for measuring the outcome of treatment for high-grade cervical intra-epithelial neoplasia (CIN2+). However, there is no international consensus regarding the number of tests and follow-up visits necessary in the post-treatment surveillance. A negative HPV DNA test result may permit relaxing the intensive post-treatment surveillance, but this possibility has not been standardized by all institutions to date. Study design: In 2008, the surveillance programme covering the Emilia-Romagna region in northern Italy adopted the HPV DNA test as a routine tool in the follow-up of women treated for CIN2+. Data from a prospective 5-year study are reported herein. Three hundred and ten patients treated for CIN2+ with a loop electrosurgical excision procedure underwent HPV DNA testing, cytology and colposcopy at 6 months post treatment. If all three tests were negative, women were tested at 18 months with cytology and colposcopy. If any of the three tests were positive, women were tested at 12, 18 and 24 months with cytology and colposcopy. When appropriate, a colposcopy-directed biopsy or CIN2+ retreatment was performed. After 18–24 months, the patients were tested annually with cytology for 3 years. Results: None of the 172 (55%) women who were HPV negative at 6 months were found to have residual/recurrent CIN2+ during the surveillance period. In contrast, among the 138 (45%) HPV-positive women, 17 cases of residual/recurrent CIN2+ (17/138; 12.3%) were identified between 6 and 24 months. Conclusion: HPV DNA testing at six months after treatment for CIN2+ effectively identifies women who are disease free (HPV negative), and for whom a single follow-up at 18 months is sufficient.